一种高效的预制混凝土箱梁生产线 (2023)
本申请涉及一种高效的预制混凝土箱梁生产线，属于预制混凝土构件领域，其包括流水台，所述流水台包括浇筑区和养护区，所述浇筑区处设有成型模板，所述流水台上设有传送轨道，所述传送轨道同时穿过浇筑区和养护区，所述传送轨道上滑动有转运台车，所述成型模板位于传送轨道的侧边，所述成型模板与转运台车可拆卸连接，所述流水台上且位于浇筑区还设有浇筑机构，所述浇筑机构用于向转运台车上浇灌混凝土。本申请中转运台车既作为混凝土成型的模板使用，在混泥土凝固之后又作为转运设备以携带预制箱梁向养护区移动，省去了原本的吊运过程和操作，提高了生产效率。 The invention relates to an efficient precast concrete box girder production line, and belongs to the field of precast concrete components, the efficient precast concrete box girder production line comprises a flow table, the flow table comprises a pouring area and a curing area, a forming template is arranged at the pouring area, a conveying track is arranged on the flow table, and the conveying track penetrates through the pouring area and the curing area at the same time; a transfer trolley slides on the conveying track, the forming formwork is located on the side edge of the conveying track and detachably connected with the transfer trolley, a pouring mechanism is further arranged on the flow table and located in the pouring area, and the pouring me